2000
DOI: 10.1002/1522-2683(20000701)21:12<2522::aid-elps2522>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Charaterization by two-dimensional gel electrophoresis of host proteins whose synthesis is sustained or stimulated during the course of herpes simplex virus type 1 infection

Abstract: Herpes simplex virus type 1 (HSV-1) gene expression is concomitant with a selective shutoff of host protein synthesis. While the synthesis of the vast majority of cellular proteins is inhibited immediately after infection, several cellular proteins continue to be synthesized, even during the late phase of infection. Because these cellular proteins may intervene in the life cycle of the virus, we undertook two-dimensional polyacrylamide gel electrophoresis (2-D PAGE) analyses to evaluate the proportion of cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Only a small portion of host cell proteins was altered during early stages of infection by either HSV‐1 or PRV. This finding is consistent with the earlier study using only 2DE analysis . Both studies showed that the expression levels of lamin A/C and hnRNP K were affected by infection.…”
Section: Cell Response To Viral Infectionsupporting
confidence: 93%
See 2 more Smart Citations
“…Only a small portion of host cell proteins was altered during early stages of infection by either HSV‐1 or PRV. This finding is consistent with the earlier study using only 2DE analysis . Both studies showed that the expression levels of lamin A/C and hnRNP K were affected by infection.…”
Section: Cell Response To Viral Infectionsupporting
confidence: 93%
“…Systematic studies of viral transcription profiles are useful, but they cannot report on protein composition, stability, or modifications (see for example ). Early studies compared the mock‐infected and HSV‐1‐infected cell proteome using 35 S pulse‐labeling and 2DE . While HSV‐1 infection strongly inhibited host protein synthesis, the synthesis of a number of acidic proteins and basic ribosome proteins was maintained or stimulated.…”
Section: Cell Response To Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although detailed studies have been conducted examining the roles of individual viral proteins during replication, little is known about how these events occur on a global‐proteomic level during infection. Comparative 2‐DE has been used to examine the effect of HSV‐1 infection on host ribosomal proteins 26 and vhs activity 27. Global proteomic studies have been performed on cells transformed by the Epstein–Barr virus (EBV, a member of the gammaherpesvirus family) 28 and more recently on cells infected with Pseudorabies virus (a member of the alphaherpesvirus family) 29.…”
Section: Introductionmentioning
confidence: 99%
“…SPD is found in the envelope and SPM in the nucleocapsid (17). We have identified one of the cellular proteins that we have shown previously to escape the virally induced shutoff of cellular protein synthesis (14) as being ornithine decarboxylase (ODC) (unpublished results). ODC is one of the key enzymes of the polyamine biosynthetic pathway.…”
mentioning
confidence: 98%